Investigating corrosion charateristics of Electroplated medium carbon steel in sodium carbonate environment for decorative objects applications (2013)
The main objective of this study is to investigate the corrosion resistance characteristics of electroplated Medium Carbon Steel (MCS) in 0.5mol/dm3 Sodium Carbonate environment. Nickel plating of MCS was done in watts solution for 25 minutes with a current density of 3 A/dm3 at 60oC. The nickel plated MCS was later gold plated for 20 minutes with a current density of 0.2 A/dm3 at 50oC . The plated and unplated MCS were exposed to sodium carbonate environment for 360 hours. The weight loss was taken every 24 hours in order to estimate corrosion penetration rate (CPR). The results obtained showed that plated MCS generally showed a better corrosion resistance than the unplated one. Although gold plated MCS has a slightly better corrosion resistance characteristic than nickel plated one, the conclusion that can be drawn from this study is that Nickel and Gold plated medium carbon steels are found to be both reliable materials for decorative objects applications in sodium carbonate environment.